2020
DOI: 10.3892/or.2020.7561
|View full text |Cite
|
Sign up to set email alerts
|

RNF43 mutation is associated with aggressive tumor biology along with BRAF V600E mutation in right-sided colorectal cancer

Abstract: Right-sided colorectal cancer (RCRC) demonstrates worse survival outcome compared with left-sided CRC (LCRC). Recently, the importance of RNF43 mutation and BRAF V600E mutation has been reported in the serrated neoplasia pathway, which is one of the precancerous lesions in RCRC. It was hypothesized that the clinical significance of RNF43 mutation differs according to primary tumor sidedness. To test this hypothesis, the clinicopathological characteristics and survival outcome of patients with RNF43 mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
2
18
2
Order By: Relevance
“…Notably, reduced RNF43 function is a negative prognosis factor in gastric cancer patients (Gao et al, 2017;Neumeyer et al, 2019a;Niu et al, 2015) and RNF43 loss of function type of mutation exacerbated Helicobacter pylori-induced gastric tumor carcinogenesis associated with the upregulation of WNT5A mRNA level (Katoh, 2007;Li et al, 2014;Neumeyer et al, 2019b;Peek and Crabtree, 2006). Further, in colorectal cancer RNF43 mutations were found to associate with BRAF V600E mutation (Matsumoto et al, 2020;Yan et al, 2017).These results suggest the existence of more universal functional WNT5A-RNF43 axis where RNF43 acts as a gatekeeper guarding the abnormal procancerogenic noncanonical Wnt pathway activation.…”
Section: Discussionmentioning
confidence: 88%
“…Notably, reduced RNF43 function is a negative prognosis factor in gastric cancer patients (Gao et al, 2017;Neumeyer et al, 2019a;Niu et al, 2015) and RNF43 loss of function type of mutation exacerbated Helicobacter pylori-induced gastric tumor carcinogenesis associated with the upregulation of WNT5A mRNA level (Katoh, 2007;Li et al, 2014;Neumeyer et al, 2019b;Peek and Crabtree, 2006). Further, in colorectal cancer RNF43 mutations were found to associate with BRAF V600E mutation (Matsumoto et al, 2020;Yan et al, 2017).These results suggest the existence of more universal functional WNT5A-RNF43 axis where RNF43 acts as a gatekeeper guarding the abnormal procancerogenic noncanonical Wnt pathway activation.…”
Section: Discussionmentioning
confidence: 88%
“…RNF43 mutations are associated with microsatellite-instable tumors and are mutually exclusive with inactivating APC mutations [ 26 ]. Recurrent RNF43 mutations are predicted to create neopeptides [ 22 , 27 ] and have been associated with aggressive tumor biology [ 28 ]. The high frequency of the RNF43 G659fs variant suggested it could have a different functional impact than other truncating variants.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that CRCs found in the right side of the colon show the MSI‐high phenotype, concentrated BRAF‐RNF43 mutations, and poor prognosis due to a lack of response to standard chemotherapy and the metastatic nature of the cancer cells, whereas CRCs in the left side have a better prognosis associated with the MSS phenotype and frequent APC‐KRAS mutations. [ 91–93 ] It is known that the right side of the colon (from the duodenum to two‐third of the transverse colon) originates from the midgut during embryogenesis, whereas the left side of the colon (from one‐third of the transverse colon to the anal canal) originates from the hindgut (Figure 3). [ 94 ] These facts suggest that the difference of gene mutation subsets between BRAF‐RNF43 and APC‐KRAS may be related to the different embryonic origins of the cells in these two regions.…”
Section: Roles Of Rnf43 and Znrf3 In Tumorigenesismentioning
confidence: 99%